Analisis Sentimen pada Twitter menggunakan Word Embedding dengan Pendekatan Word2Vec - Hastari Utama; Ahlihi Masruro (Jurnal Sistem Cerdas, 2022)
In this day and age, the use of social media is familiar to some circles. The existence of social media can be analyzed for certain interests. This analysis can also be carried out for the benefit of knowing the opinions or sentiments that contain it. Therefore, a sentiment analysis is needed to get a classification of existing opinions. The use of sentiment analysis cannot be separated from the document or text representation stage. This usually takes the form of the bag of word (BOW). However, BOW has a weakness, namely it produces a lot of features so that the classification accuracy results are less than optimal. Therefore we need the Word Embedding method to represent documents in vector form. The use of this method results in fewer features so that data training time can be shorter. Apart from that, the syntax and semantics of the words that compose the tweet are also considered. So, Word Embedding produces meaningful vectors.